THE CONCEPT OF SUSPENDING AND TERMINATING PROCEEDINGS IN CIVIL PROCEEDINGS, AS WELL AS THE CONSEQUENCES OF SUSPENDING PROCEEDINGS - Abdibaeva Jamila Aqpolat qizi (Scholar Express Journals, 2025)
This article explores the theoretical and legal foundations of suspending and terminating proceedings in civil litigation, as well as the circumstances under which they are applied and their legal consequences. According to civil procedural legislation, proceedings may be suspended either mandatorily or at the discretion of the court. In such cases, the court is not permitted to undertake any procedural actions except those aimed at securing evidence or claims. Termination of proceedings, on the other hand, marks the final conclusion of court consideration, after which refiling the same claim between the same parties is not allowed. The article analyzes the relevant provisions of the Civil Procedure Code of the Republic of Uzbekistan and includes a comparative overview of practices in foreign jurisdictions
Keywords: Suspension of proceedings; termination of proceedings; procedural actions